Automatic coin counting using image processing - Mohd Syafarudy, Abu; Lim, Eng Aik (Universiti Putra Malaysia (UPM), 2011)
Organized by Jabatan Matematik Fakulti Sains, Universiti Putra Malaysia, 15th - 17th Disember 2009 at Mahkota Hotel, Melaka, Malaysia.